A Formal Protocol to Conduct Usability Heuristic Evaluations in the Context of the Software Development Process - Paz, Freddy; A. Paz, Freddy; Antonio Pow-Sang, José; Collazos, César (International Journal of Engineering and Technology, 2018)
Heuristic evaluation is one of the most used techniques to evaluate the level of usability of a software product. In this research, we performed a comprehensive analysis of the recent studies which report the use of this method in the context of a software development process. The purpose was to identify the specific way in which each author performs this usability evaluation method, in order to propose a formal protocol. After an indeed examination of these studies, we have determined there are several differences in the way this technique is conducted according to the literature. There is no agreement about the number of inspectors that should participate, the usability principles that should be used, the profile of the specialists who must be part of the assessment team, or the evaluation process that should be followed. This work highlights the available settings and a detailed procedure to perform a heuristic evaluation in the domain of software products.